2020
DOI: 10.18502/jss.v5i1.4566
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mindfulness-based Cognitive Therapy on Sleep Quality of Students with Social Anxiety Disorder

Abstract: Background and Objective: Anxiety disorders are usually accompanied with sleep disorders. Since limited studies have focused on the effectiveness of mindfulness-based cognitive therapy (MBCT) on anxiety-related problems such as sleep disorders, the current research was conducted to investigate the effectiveness of this intervention on sleep problems. Materials and Methods: This study was a clinical trial with control and treatment groups. The sample consisted of 24 university students diagnosed with soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…Regarding the second part of the mediation effect, higher levels of social anxiety were associated with poorer sleep quality in college students, which is consistent with prior studies ( Mohammadi et al, 2020 ). This result further validates the cognitive maintenance model of insomnia ( Harvey, 2002 ), wherein an individual’s anxiety triggers their attention and monitoring of their negative emotions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the second part of the mediation effect, higher levels of social anxiety were associated with poorer sleep quality in college students, which is consistent with prior studies ( Mohammadi et al, 2020 ). This result further validates the cognitive maintenance model of insomnia ( Harvey, 2002 ), wherein an individual’s anxiety triggers their attention and monitoring of their negative emotions.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, social anxiety, as an important indicator of mental health, is closely related to sleep quality; participants with social anxiety disorder reported poorer sleep quality than healthy participants did ( Horenstein et al, 2019 ; Mohammadi et al, 2020 ). The maintenance cognitive model of insomnia highlights that anxiety states trigger the individual’s selective attention and monitoring of internal and external sleep-related threat cues, leading to an overestimation of the extent of the perceived sleep deficit and daytime performance reduction ( Harvey, 2002 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Previous studies employing the CAMM have provided evidence that mindfulness training significantly improves the levels of mindfulness among adolescents, with effect sizes ranging from small to moderate (e.g., Bluth & Eisenlohr-Moul, 2017 ; Bluth, Roberson, & Gaylord, 2015 ; Tan & Martin, 2013 ). In addition, the results coincide with those of meta-analytic studies on the effects of MBCT on depression ( Goldberg et al., 2019 ; Kuyken et al., 2016 ; McCartney et al., 2021 ) and RCTs on sleep disorders ( Camino et al., 2022 ; Javadi & Ghorbani, 2019 ). Although the effects of MBCT interventions on depression and sleep disorders have been well established, these studies have mainly focused on adults, especially patients who were clinically diagnosed with depressive disorder, generalized anxiety disorder, or sleep disorders (e.g., Javadi & Ghorbani, 2019 ; Nikkhah et al., 2019 ).…”
Section: Discussionsupporting
confidence: 79%
“…Many studies have demonstrated the effectiveness of MBCT in reducing depression ( Goldberg et al., 2019 ; Simonsson, Bazin, Fisher, & Goldberg, 2021 ) and sleep disorders ( Javadi & Ghorbani, 2019 ; Nikkhah, Haghani, & Aghaali Tari, 2019 ). For instance, meta-analytic studies have demonstrated the efficacy of MBCT in reducing depression in patients in remission ( Kuyken et al., 2016 ) and preventing depression relapse in the long term ( McCartney et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation